UP TO DATE ANTIPLATELET THERAPY IN PATIENTS WITH HIGH RISK OF THROMBOTIC EVENTS AND REAL CLINICAL PRACTICE - S. Yu. Martsevich; V. P. Voronina; M. L. Ginzburg; N. P. Kutishenko; Yu. N. Polyanskaya; T. G. Kheliya; A. M. Malysheva; S. N. Tolpygina; V. S. Kutuzova; E. A. Gofman; A. D. Deev (Рациональная фармакотерапия в кардиологии)
Aim. To assess the real rate of dual antiplatelet therapy (DAT, acetylsalicylic acid + clopidogrel) use in patients having appropriate indications according to current clinical guidelines and to study the possibility of prescription rate improvement by education activity directed to doctors. Material and methods. The study consisted of 3 parts. Parts I and II present the results of two questionnaire surveys of patients with acute myocardial infarction, or stenting, who needed in DAT according to current clinical guidelines. The real use of the DAT was assessed in part III on the basis of the multicenter study conducted in different regions of Russia (ROMB study) in a large sample of patients having DAT indications. Results. Part I - PROGNOZ-IBS study. According to the questionnaire survey only 112 out of 239 patients (47%) having an absolute indications, received DOT. Part II - phone survey of patients with acute myocardial infarction in two towns of Lyubertsy and Podolsk. 28 of 71 patients (39%) took the DAT (from some days to 6 months) and 35 patients (49%) — did not take it. Part III - ROMB study. 519 patients did not take DAT, at that 259 (50%) in hospital and 260 (50%) - in out-patient clinic. 521 patients took DAT according to indications, at that 238 (46%) in hospital and 283 (54%) - in out-patient clinic. Conclusion. Less than 50% of patients, having direct indications, received DAT in the real clinical practice. The prescription rate can be improved due to education activity directed to doctors and increase in clopidogrel drugs affordability.